Pembuatan Vidio Profil Sebagai Penunjang Informasi Dan Promosi Cagar Budaya Di Lombok Tengah - Suhaini Suhaini; Sofiansyah Fadli; Maemun Saleh; Lalu Mutawalli; Hairul Fahmi; Maulana Ashari; Saikin Saikin (Jurnal ABDIMAS Budi Darma, 2022)
Indonesia is one of the countries with the most favorite tourist objects in the world. There are many cultures, customs and natural beauty that are still preserved. One type of tourism that is closely related to history and ancestral heritage is cultural heritage. Cultural heritage has a high historical value and witnesses the civilization of life on earth. One of the districts in West Nusa Tenggara, namely Central Lombok Regency, has 150 cultural heritages spread across various sub-districts. 7 of these cultural heritages have been recorded at the national and even international levels. However, due to limited sources of information and access to cultural heritage sites, tourists and local people do not know the locations and history of the cultural heritage sites. So that research is carried out with the aim of obtaining valid data and information to be promoted in the form of videos that can be watched by anyone, anywhere and anytime via YouTube and can be used as a medium of learning about the life history of the ancestors of the Sasak tribe in Central Lombok Regency.In the research conducted, the researchers collected data and information by means of literature study, observation and direct interviews to cultural heritage locations and the Tourism Office of Central Lombok Regency. Method of analysis with SWOT (Strengths, Weaknesses, Opportunities, Threats). The design method uses the multimedia production process flow method with Adobe Audition software as audio editing and Adobe Premiere Pro 2020 as video editing. And the questionnaire test is used to obtain responses from the respondents by calculating the Likert scale